Improving Teacher Professional Commitment Through Empowerment, Compensation, and Self-Efficacy: A Correlation Study with SITOREM Analysis on Private Junior High School Teachers in Cibinong District - Wahidah, Nurul; Patras, Yuyun Elizabeth; Ikhsan, Ikhsan (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
The reality in the field is that a person who works as a teacher has not committed to his profession; Just like there are still teachers who teach more than one school, there are still teachers who do additional tasks besides teaching, and so on. This study examines the Improvement of Teacher Professional Commitment Through Strengthening Empowerment, Compensation, and Self-Efficacy (Correlation Study and SITOREM Analysis on Permanent Teachers of Private Junior High Schools (GTY) in Cibinong District, Bogor Regency). This research method is quantitative. The study showed that the research positively influenced empowerment (X1) with teacher innovation. (2) Then, the research hypothesis is that there is a positive influence of compensation on teacher professional commitment; (3) Based on the research hypothesis, there is a positive influence of self-efficacy on the commitment of the teacher profession; (4) Based on the research hypothesis, there is a positive influence of empowerment and compensation on teacher professional commitment; (5) Based on the research hypothesis, there is a positive influence of empowerment and self-efficacy on professional commitment; (6) Based on the research hypothesis, there is a positive influence of compensation and self-efficacy on teacher professional commitment; and (7) Based on the research hypothesis, there is a positive influence of empowerment, compensation, and self-efficacy together on teacher professional commitment.